A imagem do Estado do Piauí na perspectiva do marketing de lugar - Lima, Maria de Fátima de Oliveira (2017)
The study aims to understand the meaning produced about the State of Piauí as a mark of a place and an integral part of the Brazilian nation. The State contrasts with others from the same region of the country, regarding economic indexes, quality of life and social welfare, although it has attractions that constitute potential natural and cultural assets of tourism exploration. It is hypothesized that, independent of its geopolitical, historical and cultural formation, the image of Piauí results from variants in the scope of communication, since many agents operate on the elements that construct their simulacrum of identity, leading, thus, to a negative perspective on the place. In this process, it is important to know how the state's action was promoted by the last two state governments, by the media focused on the dissemination of local attractions, both interested in promoting tourism. Taking as a basis the approach of communication in the field of brand formation, specifically the one that deals with place branding, by authors such as Kapferer, Kotler, Kavaratiz and Ashworth is intended to construct a critical vision of the strategies of building a brand of place (taken from the analysis of official IBGE data and other sociodemographic research institutes), which result in biases that are detrimental to a positive image of Piauí, or that reveals the erasures of attractive elements to the tourism and the people from Piauí. Among institutional and private discourses, the analysis proposes to understand which values are highlighted according to the interests of each group and how this shows an imbalance in the use of communication techniques to the detriment of inhabitants and the image of that State